I am having trouble with this question:

Calculate the length of the astroid of $x^{\frac23}+y^{\frac23}=1$. s = ?

I approached it by doing the following:

  1. setting $x^{\frac23}=1$ because then I can find $x=\sqrt{1}=1$
  2. Then I set $$s = 4\int_0^1 \sqrt{1 + \left(\frac{dy}{dx}\right)^2}dx$$
  3. Then I did implicit differentiation to get

$$\frac23 x^{-\frac13} + \frac23 y^{-\frac13}\left(\frac{dy}{dx}\right) = 0,\\ \frac{dy}{dx} = -\left(\frac{y}{x}\right)^{\frac13}.$$

I stopped there... I appreciate the help. Thank you!

  • $\begingroup$ Can you write $y$ as a function of $x$, i.e., $y=f(x)$? $\endgroup$ – David H Apr 12 '14 at 22:14

$$ds^2=dx^2+dy^2$$ $$ds=\sqrt{dx^2+dy^2}=\sqrt{1+\left(\frac{dy}{dx}\right)^2}dx$$ $$s=\int \sqrt{1+\left(\frac{dy}{dx}\right)^2}dx$$

You had the right approach, but the problem was with the implicit differentiation. Since you have $y$ in there, it becomes a problem when integrating.

Instead, isolate $y$ from the original and take the derivative of that: $$x^{\frac23}+y^{\frac23}=1$$ $$y^{\frac23}=1-x^{\frac23}$$ $$y=\left(1-x^{\frac23}\right)^\frac32$$

Now when you find $\frac{dy}{dx}$, it will only be in terms of $x$. So take the derivative of that: $$\frac{dy}{dx}=\frac32 \left(1-x^{\frac23}\right)^\frac12 \left(-\frac23x^{-\frac13}\right)$$

Get rid of the fractions:

$$\frac{dy}{dx}=\left(1-x^{\frac23}\right)^\frac12 \left(-x^{-\frac13}\right)$$

Now plug it in:

$$s=4\int_0^1 \sqrt{1+\left(\left(1-x^{\frac23}\right)^\frac12 \left(-x^{-\frac13}\right)\right)^2}dx=4\int_0^1 \sqrt{1+\left(\left(1-x^{\frac23}\right)^\frac12 \left(-x^{-\frac13}\right)\left(1-x^{\frac23}\right)^\frac12 \left(-x^{-\frac13}\right)\right)}dx=4\int_0^1 \sqrt{1+\left(\left(1-x^{\frac23}\right) \left(x^{-\frac23}\right)\right)}dx=4\int_0^1 \sqrt{1+\left(x^{-\frac23}-1\right)}dx=4\int_0^1 \sqrt{x^{-\frac23}}dx=4\int_0^1 x^{-\frac13}dx$$

So easy to integrate now!

$$s=4\int_0^1 x^{-\frac13}dx=4\left(\frac32x^\frac23\Biggr|_0^1\right)=4\left(\frac32\right)=\therefore 6$$


A potentially easier way to do this is to parametrize the astroid by taking advantage of the trig identity $\cos^2(\theta)+\sin^2(\theta) = 1$.

Take $x = \cos^3(t)$ and $y = \sin^3(t)$ where $0\leq t \leq 2\pi$.

By symmetry, we can simply find the arclength of $1/4$th the astroid and multiply by $4$ at the end. The bounds on our integration will be $0 \leq t \leq \pi/2$.

Now simply use the formula for arclength:

$$\int_0^{\pi/2} \sqrt{\left( \frac{dx}{dt}\right)^2 + \left( \frac{dy}{dt} \right)^2} \ dt$$

  • $\begingroup$ Thank you very much! This was very helpful! $\endgroup$ – Vanessa Vitiello May 8 '14 at 22:40

You can also continue using your formula for s.


When you fill in $\frac{dy}{dx} = -\frac{y^\frac{1}{3}}{x^\frac{1}{3}}$ in $s$, you get

$$s=4\int_0^1 \sqrt{1+\left(\frac{y^\frac{1}{3}}{x^\frac{1}{3}}\right)^2}dx$$

$$s=4\int_0^1 \sqrt{\frac{x^\frac{2}{3}+y^\frac{2}{3}}{x^\frac{2}{3}}}dx$$

$$s=4\int_0^1 \frac{1}{x^\frac{1}{3}}\sqrt{x^\frac{2}{3}+{y^\frac{2}{3}}}dx$$

But the original formula says that $x^\frac{2}{3}+y^\frac{2}{3}=1$, so

$$s=4\int_0^1 \frac{1}{x^\frac{1}{3}}dx=4\int_0^1 x^\frac{-1}{3}dx=4\left(\frac{3}{2}\right)=6$$

  • $\begingroup$ Great answer and welcome to Mathematics Stack Exchange! A quick tour will enhance your experience. $\endgroup$ – dantopa Jan 24 '19 at 15:55

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.